Financial Sustainability for Nonprofit Organizations A Review of the Literature - Sontag-Padilla, Lisa M. (RAND Corporation, 2012)
Nonprofits face a myriad of challenges in establishing and maintaining financial sustainability, and these challenges are exacerbated for nonprofits serving low-resources, high-need communities. This literature review identifies key themes and findings that may inform operations and decisionmaking related to improving sustainability in such organizations.